Factors Affecting the Survival of Patients with Oligometastatic Non-Small-Cell Lung Cancer: A Meta-Analysis. (19th May 2019) - Shi, Yu; Yang, Jianxin; Yao, Ninghua; Shao, Minghai; Ding, Wenxiu; Jiang, Wanrong; Sun, Xinchen
Abstract : Background . The aim was to investigate the potential factors related with overall survival of oligometastatic non-small-cell lung cancer (NSCLC) patients. Methods . A literature search was conducted in databases including PubMed, Embase, and Cochrane library up to March 2017. The hazard radio (HR) as well as the corresponding 95% confidence interval (CI) were calculated, and all the statistics analysis was performed by the R 3.12. Heterogeneity was analyzed using I-squared and Cochran Q tests. Furthermore, sensitivity analysis was performed to evaluate the stability of results. Results . In total, 6 articles were included in the meta-analysis. Nodal status was significantly correlated with the overall survival rate of NSCLC oligometastatic patients (HR: 1.69, 95% CI: 1.23–2.32, Z = 3.20, P = 0.001 ). No significant relationship was found between overall survival rate of NSCLC oligometastatic patients and the indicators including sex, stage, smoker, age, and histology. Notably, sensitivity analysis on data evaluating relationship between patients survival and the stage and histology showed that results were reversed after removing one of the studies. Conclusions . Nodal status might be associated with the overall survival of oligometastatic NSCLC patients.